PENERAPAN MODEL PEMBELAJARAN THINK PAIR SHARE UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 16 KUALA PENASO - ', Dahlia; Marhadi, Hendri; ', Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The research was carried out starting from the low averages the fourth grade social studies students SDN 16 Kuala Penaso. Of the 23 students who achieved KKM (minimum completeness criteria) only 8 students (34,78%), while 15 students did not complete (65,22%) with an average 53,48. The research problem is Application of Cooperative Learning Model with Type Think Pair Share (TPS) to Improve Learning Outcomes in Grade IV IPS SDN 16 Kuala Penaso?